SOME PRAGMATIC POSSIBILITIES OF LANGUAGE UNITS - Hasanova Dilfuza Odilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the relationship between linguistic and non-linguistic phenomena, language and speech, dialogue and discourse, text and speech act, purpose and communication situation, linguistic opportunity and speech activity, addressee and addressee, purpose and effect of communication, communicative intention and speech situation, phenomena and concepts such as communication culture and speech etiquette appear as objects and subjects of linguistic research illuminated.